Guest editorial: a tribute to the Very Reverend Edward Shotter (FCMME) - Gillon, Raanan; Boyd, Kenneth; Brazier, Margaret; Campbell, Alastair; Goddard, Andrew; Kong, Wing May; Limerick, Sylvia; Lock, Stephen; Montgomery, Jonathan (Journal of medical ethics, 2019)
In 1963, he established the pioneering ‘Medical Group’ model (initially in London but quickly spreading across the UK), an innovative bottom-up method whereby students in the health professions could gain a grounding in ethics that had previously been denied to the profession.5 It was with these Medical Groups (presenting to and administering them) that many of the leading figures in contemporary UK medical ethics and law began their careers in the subject including Sir Kenneth Calman, Sir Ian Kennedy, Professor Margaret Brazier OBE, Professor John Harris and Professor Sir Jonathan Montgomery to name but a few. In summary, the healthy state of contemporary scholarship in medical ethics, the UK’s envied reputation for ethical governance via institutions such as the Human Genetics Commission and Human Fertilisation and Embryology Authority, and ethically informed professional education and practice can be seen as in great degree the fruits of the groundwork that Ted Shotter laid over a lifetime of service to medical ethics. Encouraged to do so by RG one of us (SL—Countess of Limerick) added a postscript to her supporting letter to the Honours Committee which we would like to recall here: Because national honours are almost never awarded posthumously, we have decided to create, and award to Ted, our own posthumous honour—the FCMME—for he was indeed a Founding Companion of Modern Medical Ethics.